2019
DOI: 10.1186/s12864-019-6352-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and microbiome of coconut rhinoceros beetle (Oryctes rhinoceros) larvae

Abstract: BackgroundThe coconut rhinoceros beetle, Oryctes rhinoceros, is a major pest of palm crops in tropical Asia and the Pacific Islands. Little molecular data exists for this pest, impeding our ability to develop effective countermeasures and deal with the species’ growing resistance to viral biocontrols. We present the first molecular biology analyses of this species, including a metagenomic assay to understand the microbiome of different sections of its digestive tract, and a transcriptomics assay to complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 86 publications
0
36
0
Order By: Relevance
“…A broader study should be performed to discriminate among some potential tissues where components of the insect humoral immune system are known to be expressed [46][47][48][49] , such as fat body, haemocytes, gut, salivary glands, trachea, Malpighian tubules, and integument. Fat bodies have been reported to display high expression level for some AMP types such as defensins 49,50 and attacin 51 . Defensin genes from adult A. stephensi are expressed in fat body, midgut, haemolymph and salivary glands with the high level of expression at fat body 49 .…”
Section: Discussionmentioning
confidence: 99%
“…A broader study should be performed to discriminate among some potential tissues where components of the insect humoral immune system are known to be expressed [46][47][48][49] , such as fat body, haemocytes, gut, salivary glands, trachea, Malpighian tubules, and integument. Fat bodies have been reported to display high expression level for some AMP types such as defensins 49,50 and attacin 51 . Defensin genes from adult A. stephensi are expressed in fat body, midgut, haemolymph and salivary glands with the high level of expression at fat body 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The complete mitogenome sequence was initially annotated using the MITOS web server (Bernt et al 2013), and tRNA genes and their secondary structures were cross-analysed using tRNAscan-SE v2.0 (Chan et al, 2019). To further refine the annotation and to examine mitogenome transcription, we used BWA-MEM to align Illumina reads from a transcriptome study of O. rhinoceros larvae (Shelomi, Lin, and Liu 2019), retrieved from the NCBI (SRR9208133). Finally, we manually inspected and compared our annotation to the complete and near complete mitogenome annotations of other related taxa (Table 1) in Geneious (2020.0.4).…”
Section: Genome Assembly Annotation and Analysismentioning
confidence: 99%
“…A study on important role of Collembola as a decomposer of soil organic matter by Rahardjo, Rachmawati, & Soetjipto (2019) inspiring to study the role of rhinoceros beetle larvae as a decomposer in the oil palm plantations. Shelomi, Lin, & Liu, (2019) reported that the gut microbiota of O. rhinoceros larvae is quite similar to that of the termite gut, as both species feed on decaying wood. Moreover, the beetle larvae are suggested to be used as feed and food (Okaraonye & Ikewuchi, 2009;Omotoso, 2018).…”
Section: Introductionmentioning
confidence: 99%